2022
DOI: 10.3390/healthcare10101852
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Practice, Compliance, and Barriers toward Ventilator-Associated Pneumonia among Critical Care Nurses in Eastern Mediterranean Region: A Systematic Review

Abstract: Background: Ventilator-associated pneumonia (VAP) has been identified as a serious complication among hospitalized patients and is associated with prolonged hospitalizations and increased costs. The purpose of this study was to examine the knowledge, practices, compliance, and barriers related to ventilator-associated pneumonia among critical care nurses in the eastern Mediterranean region. Methods: The PRISMA guidelines guided this systematic review. Four electronic databases (EMBASE, MEDLINE (via PubMed), SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Previous research stated that increasing the level of education would have an impact on the knowledge, attitudes, and practices of nurses in providing care and making optimal decisions [ 13 ]. However, comprehensive training on VAP is needed to increase the knowledge, compliance, and practice levels of critical care nurses [ 14 ]. Increasing the quality of care and preventing VAP can have an impact on improving patients’ quality of life [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research stated that increasing the level of education would have an impact on the knowledge, attitudes, and practices of nurses in providing care and making optimal decisions [ 13 ]. However, comprehensive training on VAP is needed to increase the knowledge, compliance, and practice levels of critical care nurses [ 14 ]. Increasing the quality of care and preventing VAP can have an impact on improving patients’ quality of life [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, if clinical practice is to be advanced, the experience could help students to recognize the value of nursing as early as possible. A systematic review by Al‐Mugheed, Bani‐Issa, et al ( 2022 ), Al‐Mugheed, Bayraktar, et al ( 2022 ). has reported that shortage of nursing knowledge is one of the common barriers encountered in clinical practice settings.…”
Section: Discussionmentioning
confidence: 99%
“…Registered nurses need to have adequate understanding and knowledge underpinning their practice to ensure safe and proactive patient care (Craft et al, 2017 ). It is necessary to improve the knowledge and safety attitude of nurses to increase health care quality (Al‐Mugheed, Bani‐Issa, et al, 2022 ; Al‐Mugheed & Bayraktar, 2020 ; Al‐Mugheed, Bayraktar, et al, 2022 ). Study engagement has a strong relationship with student academic achievement and is very impactful on students' development and future careers (Park et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple factors may contribute to the inadequacy in the knowledge and practices regarding VAP and VAP 15 prevention bundle among ICU nurses. This may range from the level of academic qualification to the degree of professional experience of working in an intensive care 16,17 environment. However, disease-specific education and practical training can effectively fill-in this gap, as evident in this current study.…”
Section: Discussionmentioning
confidence: 99%